2006
DOI: 10.2134/agronj2004.0222
|View full text |Cite
|
Sign up to set email alerts
|

Soil Cover and Tillage Influenced Metolachlor Mobility and Dissipation in Field Lysimeters

Abstract: Leaching studies using soil column field lysimeters were conducted in 1991 and 1992 to determine the influence of tillage [conventional (CT) and reduced (RT)], soil cover (fallow, soybean, and bermudagrass sod), and water input level on 14C metolachlor mobility. Runoff and leachate collectors were installed. Leachate was collected weekly and analyzed for herbicide content. At 128 d after treatment (DAT), the lysimeters were removed, and the soil was analyzed for herbicide concentration as a function of depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…VII). Although most of these works showed greater losses under conservation tillage Isensee et al, 1990;Masse et al, 1998;Singh et al, 2002;Weber et al, 2006), results are contrasted, some of them indicating no effect of tillage (Clay et al, 1998;Fomsgaard et al, 2003;Gaynor et al, 2000;Granovsky et al, 1993;Weed et al, 1995), or even greater losses under conventional tillage (Düring and Hummel, 1993;Gish et al, 1995;Levanon et al, 1993).…”
Section: Leachingmentioning
confidence: 97%
See 1 more Smart Citation
“…VII). Although most of these works showed greater losses under conservation tillage Isensee et al, 1990;Masse et al, 1998;Singh et al, 2002;Weber et al, 2006), results are contrasted, some of them indicating no effect of tillage (Clay et al, 1998;Fomsgaard et al, 2003;Gaynor et al, 2000;Granovsky et al, 1993;Weed et al, 1995), or even greater losses under conventional tillage (Düring and Hummel, 1993;Gish et al, 1995;Levanon et al, 1993).…”
Section: Leachingmentioning
confidence: 97%
“…Volatilisation directly depends on environmental conditions and is favoured first by high temperatures (Glotfelty, 1987;Weber et al, 2002) and also by wet soils that keep the molecules available in water solution. Weber et al (2006) observed during a year of monitoring that volatilisation reached 22 and 32% of applied metolachlor in conservation tillage and conventional tillage, respectively. Due to the mulch, soil surface water content was higher under conservation tillage, which slowed down the soil warming and thus reduced the amount of herbicide lost.…”
Section: Volatilisationmentioning
confidence: 99%
“…The atrazine herbicide shows less leaching in a no-tillage system, when compared to conventional tillage (Weber et al 2006b), likely due to the fact that the plant cover exhibits greater sorption capacity than the soil.…”
Section: Abstract Resumomentioning
confidence: 99%
“…Losses due to leaching are considered to be more important in these systems because of greater water infiltration and development of macropores, which can induce preferential flow. Greater leaching losses of metolachlor, atrazine and other herbicides were reported, which were attributed to the development and preservation of macropores formed by roots and earthworm burrows under no‐tillage practices . Meanwhile, reduced leaching of insecticides and many herbicides was also reported and was attributable to their greater retention in surface soil owing to increased organic matter content .…”
Section: Introductionmentioning
confidence: 99%